(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
Digital technologies and the internet have revolutionized business operations and consumer interactions with brands. Personalized marketing, driven by data collection, analysis, and targeted strategies, tailors content and recommendations to individual consumers based on their unique characteristics, interests, and behaviors. This study explores the impact of personalized marketing on customer perceptions and engagement in the digital economy, with emphasis on building trust, enhancing credibility, strengthening brand image, and improving customer retention. Utilizing a quantitative-correlational research design, the researchers gathered data from 50 customers through convenience sampling. The respondents were evaluated based on their demographic profiles, including age, gender, civil status, and employment status. The results showed that the majority of respondents were aged 21–30 years (40%), with females comprising a higher percentage (56%). Most respondents were single (76%) and identified as students (48%). In terms of personalized marketing’s influence on customer perception and engagement, respondents agreed on its effectiveness in building trust (mean = 3.56), establishing credibility (mean = 3.42), enhancing brand image (mean = 3.15), and improving customer retention (mean = 3.44). Hypothesis testing revealed a statistically significant relationship between respondents’ demographic profiles and their perception and engagement with brands. The study recommends that businesses build customer satisfaction and long‑term loyalty by consistently delivering on their promises and offering genuine value. In personalized marketing, the focus should be on empowering customers to make informed decisions rather than pressuring them into unwanted purchases. Furthermore, companies must present the terms and conditions of personalized promotions in a clear, transparent, and easily understandable manner.